2002
DOI: 10.1021/jm010365+
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Structure−Activity Relationship of 2-Aminobenzophenone Derivatives as Antimitotic Agents

Abstract: A new type of inhibitor of tubulin polymerization was discovered on the basis of the combretastatin molecular skeleton. The lead compounds in this series, compounds 6 and 7, strongly inhibited tubulin polymerization in vitro and significantly arrested cells at the G(2)/M phase. Compounds 6 and 7 yielded 50- to 100-fold lower IC(50) values than did combretastatin A-4 against Colo 205, NUGC3, and HA22T human cancer cell lines as well as similar or greater growth inhibitory activities than did combretastain A-4 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
63
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 116 publications
(66 citation statements)
references
References 28 publications
3
63
0
Order By: Relevance
“…CA-4P (disodium combretastatin-A-4 -3-O-phosphate), a water-soluble prodrug, is a novel antitumor vascular targeting agent and is the first combretastatin analog to enter clinic trials (10,11). Our previous work showed that 2-aminobenzophenone types of CA-4 analogs exhibited strong cytotoxic activity against a wide variety of human cancer cells, including MDR-positive cancer cells (12).…”
Section: Introductionmentioning
confidence: 99%
“…CA-4P (disodium combretastatin-A-4 -3-O-phosphate), a water-soluble prodrug, is a novel antitumor vascular targeting agent and is the first combretastatin analog to enter clinic trials (10,11). Our previous work showed that 2-aminobenzophenone types of CA-4 analogs exhibited strong cytotoxic activity against a wide variety of human cancer cells, including MDR-positive cancer cells (12).…”
Section: Introductionmentioning
confidence: 99%
“…3-Methoxy-2-aminobenzophenone (3) and 3-cyano-2-aminobenzophenone (4) were prepared as previously described. [18,19] 3-Acetyl-N-ethylcarbazole (1) was easily synthesized via a Friedel-Craft acylation reaction. Deep-blue emitting materials, PhQ-CVz, MeOPhQ-CVz, and CN-PhQ-CVz, were prepared by an acidcatalyzed Friedlander condensation reaction.…”
Section: Synthesis and Characterizationmentioning
confidence: 99%
“…The inhibitory role of benzophenone analogues against tumor growth is mediated through a direct effect on tumor cells that results in cell cycle arrest, differentiation, or apoptosis [28,29]. Combretastatin A-4, a benzophenone analogue exhibits a selective toxicity for proliferating endothelial cells in-vitro by induction of apoptosis and vascular shut down in human cancer models in-vivo [30]. Earlier we have reported the synthesis, in-vivo antitumor and proapoptotic activity of (2-aroyl-4-methylphenoxy) acetamides 4a-e, a benzophenone analogues [31].…”
Section: Introductionmentioning
confidence: 99%